Twenty years of Tourism Geographies: a bibliometric overview. Issue 5 (20th October 2019) - Merigó, José M.; Mulet-Forteza, Carles; Valencia, Cristina; Lew, Alan A.
Abstract: Tourism Geographies is a prominently ranked journal that emerged from activities of the Tourism Commission of the International Geographical Union. It is indexed in the 'Tourism, Leisure and Hospitality Management' and 'Geography, Planning and Development' fields in the Scopus database and published its 20th volume in 2018. A bibliometric assessment of the articles and authors who have contributed to Tourism Geographies over its first two decades highlights major trends and dominant issues covered by the journal's content. Key indicators include the most published and most cited authors and articles, the institutions and countries that those authors are affiliated with, other academic journals that are closely linked to the journal through citations, and the most used keywords in the journal. The Scopus database provides access to these basic bibliometric data, while the VOSviewer software enables graphical analyses and displays of co-citations, co-occurrences of keywords, and bibliographic couplings (shared references) across papers and authors. Overall, Tourism Geographies is closely linked to other leading journals indexed by Scopus in the 'Tourism' and 'Geography' fields and publishes papers from around the world. Research topics that have been most prominent in the journal include tourism development, tourist destinations, tourist attractions, heritage tourism, tourism perceptions, sustainable tourism, and travel behavior. Among the most viewed individual papers have been those addressing issues related to sustainability, poverty issues (related to tourism in poor areas, volunteering, sustainable tourism, and the environment), and community planning (sustainable tourism planning, tourist routes and movement, and new locations for tourism development).